The War of National Liberation Army in the Karadak of Kumanovo in 2001 ( Republic of Macedonia) According to the British Press - Iseni, Fati (Richtmann Publishing, 2012)
The war of 2001 in Macedonia drew the attention of all governments and diplomacies of the superpowers of the world andalso raised curiosity of many political and military analysts and researchers who wrote about Modern and Contemporary Balkanhistory. But it seems that the journalists from the powerful countries of the world in which global politics are created, show interest tofollow the tragic events in Macedonia during 2001, war between Macedonian Army and Police forces against National Liberation Army -NLA (of Albanians). U.S. and UK in particular and the European Union were generally engaged in Macedonia politically and militarythroughout the fighting. Also British journalists and media were seriously interested from both printed and electronic ones who did notdelay and arrived at the scene immediately after this